login
a(0) = a(1) = a(2) = 1; a(n) = a(n-3) + Sum_{k=0..n-4} a(k) * a(n-k-4).
4

%I #5 Apr 11 2021 16:14:59

%S 1,1,1,1,2,3,4,6,10,16,25,40,66,109,179,296,495,831,1396,2353,3985,

%T 6770,11523,19657,33621,57633,98969,170245,293371,506371,875284,

%U 1515029,2625842,4556806,7916943,13769900,23975073,41785251,72894759,127279673,222430235,389030773,680946436,1192794189

%N a(0) = a(1) = a(2) = 1; a(n) = a(n-3) + Sum_{k=0..n-4} a(k) * a(n-k-4).

%F G.f. A(x) satisfies: A(x) = 1 + x + x^2 + x^3 * A(x) + x^4 * A(x)^2.

%t a[0] = a[1] = a[2] = 1; a[n_] := a[n] = a[n - 3] + Sum[a[k] a[n - k - 4], {k, 0, n - 4}]; Table[a[n], {n, 0, 43}]

%t nmax = 43; A[_] = 0; Do[A[x_] = 1 + x + x^2 + x^3 A[x] + x^4 A[x]^2 + O[x]^(nmax + 1) // Normal, nmax + 1]; CoefficientList[A[x], x]

%Y Cf. A001006, A050253, A307971, A343305.

%K nonn

%O 0,5

%A _Ilya Gutkovskiy_, Apr 11 2021